(untitled) (Orthodontic Journal of Nepal, 2025)
Introduction: This review aimed to provide theoretical support, based on orthodontics and mechanical engineering concepts, to emphasize the applicability and the mechanical properties involved in stainless steel, cobalt chromium, titanium-molybdenum and titanium based alloys for specialists in this field. Materials and Methods: The search strategy for articles selection was focused on PubMed and Scopus from 1963 to 2024. Results: A total of 501 citations were identified by Medline (through PubMed) and 478 by Scopus. A total of 68 articles were considered eligible for describing the basic mechanical properties of alloys and thermal tests, and tests to examine the strength of materials and the surface of the material or its crystallography. Conclusion: Metallic alloys contain specific characteristics, such as resilience, rigidity, stored energy, formability, low friction surface, low cost and biocompatibility. Stainless Steel (SS) wires have the advantage of low cost and good corrosion resistance, good resilience and good formability. Cobalt-chromium and nickel-chromium have characteristics very close to SS wires but are expensive. Titanium-molybdenum alloys revealed springback superior than SS wires, good formability and high friction coeffient. Nickel-titanium based wires present poor formability, high friction coeffient, even though some of them present the shape memory effect and superelasticity. Ti-Nb(niobium) and Timolium present intermediate properties in relation to SS and TMA wires. Aesthetic alloys are fragile to fracture and relaxation fatigue over time and are dependent on moisture absorption and temperature changes. The properties of metallic wires are function of wire composition, variables during machining process and heat treatment.